Characterisation of woven kenaf/polyester reinforced polylactic acid hybrid composites - Mohd Nor, Mohd Azlin (2023)
Growing concerns about the disposal of petroleum-based products and the demand for high-strength materials have stimulated interest in the use of biodegradable materials with higher strength for the production of hybrid composites. The objective of this study is to determine the mechanical, thermal, morphological and flammability properties of woven kenaf/polyester reinforced polylactic acid hybrid composites. The composites were fabricated by the hot-press method. The effects of different fibre contents and stacking sequences were examined. The first and second phases focused on the characterization of woven polyester-reinforced polylactic acid and woven kenafreinforced polylactic acid composites. The characterization focused on the effects of different fibre contents on both composites. Increasing the polyester fibre content in the composites resulted in the highest improvement in tensile and impact strength of the composites by up to 225% and 93%, respectively. For the woven kenaf/PLA composites, the results show that the addition of woven kenaf improved tensile properties by 47%. In the third and fourth phases, the effects of different fibre contents and stacking sequences of the hybrid composites were investigated. The sample with 4 layers of woven polyester and 1 layer of woven kenaf (S4) showed a significant percentage increase in tensile strength and elongation at break among the hybrid composites by 151% and 714%, respectively. However, the higher composition of woven kenaf in the hybrid laminated composites exhibited better flexural properties. The addition of woven polyester in the composites improved the thermal stability and degradation of the composites. In terms of flammability, the result shows that the addition of kenaf fabric was responsible for the high char yield and extended the burning time of the hybrid composites. The S5 sample with 4 layers of woven kenaf and 1 layer of woven polyester also shows the optimum viscoelastic properties such as storage modulus and loss modulus among the hybrid composites. In summary, the optimum composition for woven kenaf/polyester/PLA hybrid composites was determined for the S5 sample. All data were statistically analysed using a one-way analysis of variance and showed significant differences between the results. Overall, based on the results, these hybrid composites are suitable for use in nonload- bearing applications such as car headliners and door panels.